Self-Confidence Against Competitive Anxiety of Diving Athletes in the Training Phase - Wildhan Rahmadian Sofyan; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2024)
Psychologically, there are several factors that can reduce competitive anxiety in diving athletes, one of which is self-confidence. Unfortunately, there is still little discussion about self-confidence in diving athletes when experiencing competitive anxiety. This study aims to examine the significant relationship between self-confidence and competitive anxiety in diving athletes during the training phase. The method used in this research is descriptive with a quantitative approach using correlational. The instruments used were the State Sport-Confidence Inventory (SSCI) questionnaire and the Sport Competitive Anxiety Test (SCAT) questionnaire. The research sample consisted of 10 diving athletes from Bandung City. Data was collected via Google form in the form of a questionnaire and data analysis techniques using SPSS version 26.0. The results of data analysis show that there is a significant relationship between self-confidence and competitive anxiety in diving athletes. This research concludes that self-confidence is closely related to competitive anxiety in the training phase so that there is a relationship between self-confidence and competitive anxiety of diving athletes in the training phase.